ACCRUAL MANAGEMENT AND THE INDEPENDENCE OF THE BOARDS OF DIRECTORS AND AUDIT COMMITTEES - Abdullah, Shamsul Nahar; Nasir, Norita Mohd. (International Journal of Economics, Management and Accounting, 2013)
The recent revelation of the misleading audited accounts of several big companies in the US has heightened public concern about the integrity of a firm’s financial reporting processes. The management of the accounts is commonly known as accrual management as it is effectively accomplished through manipulation of discretionary accruals. A firm’s internal corporate governance systems should be able to constrain the extent of earnings being managed. To this end, this paper investigates one important aspect of the internal corporate governance, namely the independence of the board of directors and the audit committee. It is argued that the extent to which the board and the audit committee are independent of management determines their ability to constrain the management of discretionary accruals. Using data from the Kuala Lumpur Stock Exchange (KLSE) non-financial Main Board listed companies in 1998 evidence showed that neither board independence nor the audit committee independence effectively constrained the accrual management level. The interactive effects of board independence and audit committee independence were also found to be insignificant. Evidence in this paper, therefore, casts doubt that the independence of boards and the audit committee can lead to high quality accounting information, which is thereby useful to users. JEL classification: G34, M41 Key words: Accrual management, Audit committee independence, Discretionary accruals